Net Urinary Acid Excretion and its Association with Kidney Disease Progression in Different Stages of Chronic Kidney Disease (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Chronic kidney disease as an important public health issue. Previous studies suggest that higher urinary acid excretion is associated with progression of chronic kidney disease, but such relationship is not universally proven.Objective: To further assess such relationship between urine net acid excretion and renal outcomes in patients with chronic kidney disease, present study was designed to measure net acid excretion and to compare it with the changing stages of chronic kidney disease.Methodology: This was a cross sectional study conducted in the Department of Nephrology and Department of Biochemistry of National Institute of Kidney Diseases and Urology, Dhaka, from July 2020 to August 2021, among chronic kidney disease stage 1 to stage 5 patients who had not received dialysis as case and age and sex matched control. Patients of both gender with chronic kidney disease (stages 1-5) with urine output at least 500ml/day and age ≥ 18 years old, were enrolled in the study. Data collection sheet consisted of patient’s demographics, clinical examination and investigation result sheet. Anthropometric parameters like height and weight were measured. Systolic and diastolic BP of each patient was recorded at the time of data collection. Blood and urine samples were taken for biochemical analysis.Results: As per the selection criteria, 46 case were enrolled in the study, along with 13 age and sex matched control. Mean age of the case and control group were 51.24 ± 12.80 years and 39.38 ± 10.28 years respectively (p < 0.05). No statistically significant difference regarding net acid excretion was noticed between the case and control groups (p = 0.67). Also, no statistically significant association was found between net urinary acid excretion and different stages of chronic kidney disease. NAE was found to have statistically significant (p